Livelihood Diversification and Rural Household Economic Security in Central and Bundelkhand Regions of Uttar Pradesh, India (Indian Journal of Extension Education, 2024)
The livelihoods diversification in recent years have been characterised by a significant phenomenon, often referred to as occupational diversification. The research was carried to quantify the influence of diversifying sources of income on the financial welfare of households, as well as to evaluate the socio-economic factors that influenced the decision to pursue various livelihood choices. The systematically collected data of 480 farmers collected in August and September 2022 from Uttar Pradesh was analysed using indicator approach, multiple linear regression and the binary logistic regression model. The finding indicates that examining future lives in the context of increasing economic disparity highlights the significance of education in attaining fresh economic prospects. The results emphasise the need for urgent governmental measures that focus on education, particularly for lower social groups and economically disadvantaged individuals. These efforts should aim to provide new job prospects for these groups.